Variation in Optical Properties of Chromophoric Dissolved Organic Matter in A Shallow Lake During Rainy Season - Jiang, D.G.; Huang, Q.H.; Li, J.H.; Xiao, Y.H. (Asian Journal of Chemistry, 2011)
Variation in optical properties of chromophoric dissolved organic matter (CDOM) in a shallow lake during rainy season was investigated by UV/VIS absorption and fluorescence spectroscopy. Two humic-like components mainly from terrestrial origin (C1 and C2) and one protein-like component derived from autochthonous production (C3) were identified by applying fluorescence excitation-emission matrix combined with PARAFAC modeling. The mean values of autochthonous production and chlorophyll concentration increased from 0.28 to 0.30 μg/L and 165 to 197 μg/L, respectively. Their correlation was different in temporal pattern, demonstrating that the dominant source of autochthonous chromophoric dissolved organic matter was altered from phytoplankton to other sources such as release from sediment and runoff during the rainy season. Mean values of C1 and C2 increased significantly from 0.36 and 0.35 to 0.42 and 0.37 respectively, coupled with a (355) increasing from 2.86 m-1 to 3.86 m-1 suggesting that precipitation process may increase terrestrial chromophoric dissolved organic matter in the lake. The low values of humification index (HIX) ranging from 3.52 to 4.62 were caused by the dominant origin of autochthonous chromophoric dissolved organic matter, although input of terrestriallyderived chromophoric dissolved organic matter could make mean value of humification index increase from 3.82 to 4.35.